Nonalcoholic Steatohepatitis Challenges Hepatitis B Virus as the Leading Cause of Chronic Hepatitis in Bangladesh - Mahtab, Mamun Al; Das, Dulal Chandra; Rahim, Mohammad Abdur; Begum, Rokshana; Alam, Sheikh Mohammad Noor e; Moben, Ahmed Lutfixl; Mamun, Ayub Al; Rahman, Salimur; Akbar, Sheikh Mohammad Fazle (Bangladesh Journal of Medicine, 2017)
Background: Chronic hepatitis is inflammation of the liver that lasts at least 6 months. Knowledge of aetiology and pattern of development of complications of chronic liver disease will help in designing optimal and cost effective control measures of the disease. Methods: The present study was performed to find out the aetiological factors in patients of chronic liver disease. This was a retrospective, cross-sectional study. Patients attending Hepatology Green Unit, Bangabandhu Sheikh Mujib Medical University, Dhaka in 2014 with chronic hepatitis were included. Results: Total 3250 patients were studied, 2310(71.08%) males and 940(28.92 %) females. Most of the patients 1547 (47.6%) belong to age group of 18 to 30 years followed by 922 (28.37%) who were between the age group of 31-40 years. Majority of patients 2012(61.91%) had HBV infection, 1095(33.69%) had nonalcoholic steatohepatitis ( NASH), 81(2.49%) had HCV infection, 7(0.22%) had alcohol abuse, 28(0.86%) had Wilsons disease, 19(0.58%) had autoimmune hepatitis and no aetiological factors were recorded in 8(0.25%) patients. However in case of females 52.55 % (494/940) due to NASH, while 40.21 % (378/940) due to HBV. Conclusion: HBV infection is the major risk factor for chronic liver disease and NASH challenges HBV in our patients. Bangladesh J Medicine Jan 2017; 28(1) : 24-27